Difference in mean weight gain and hospital stay in preterm babies receiving complete or partial kangaroo mother care compared to no kangaroo mother care: Experience from a tertiary care hospital - Siddiqui, Muhammad Asif; Butt, Tayyaba Khawar; Farooq, Muhammad Azhar; Omer, Muhammad Tauseef; Zahoor, Farhan; Hussain, Komal Khadam (Journal of Fatima Jinnah Medical University, 2021)
Background: Pakistan is a resource limited country with one of the highest neonatal mortality rate (NMR) in the world. Kangaroo Mother Care (KMC) helps in reducing the mortality and improving the care of preterm babies. The objective of this study was to identify the benefits of KMC in hospitalized newborns in terms of better weight gain and early discharge from hospital. Subjects and methods: A retrospective case-control study was conducted in the Neonatal Department of Services Hospital from 01.02.2019 to 31.01.2020. A total of 144 case notes, who met inclusion criteria were included. Subjects were divided in 2 Groups of 77 each. Group 1 did not receive KMC and Group 2 received KMC (partial or complete). Admission weight, gestational age at birth, duration of hospital stay and the average weight gain was noted for subjects in both groups. SPSS version 23 was used to analyze data. Independent samples t-test was applied. A p-value of ˂0.05 is taken as significant. Results: Mean weight gain in Group 1 was 5.521 g/kg/day (±6.664), whereas in Group 2 was 15.635 g/kg/day (±9.268). Mean hospital stay in Group 1 was 12.558 days (±10.856) and in Group 2 it was 8.208 days (±6.473). Weight gain and duration of hospital stay was significantly better in KMC Group with a p-value ˂0.05. This benefit was observed both for partial and complete KMC. Conclusion: KMC (partial or complete) leads to better weight gain and reduces the duration of hospital stay.